Mathematical Reasoning of 9th-Grade Students at SMP Negeri 19 Palu in Solving Systems of Linear Equations with Two Variables: A Case Study on Gender-Based Differences - Yayuk Nurhayati; Ibnu Hadjar; Sukayasa Sukayasa; Mubarik Mubarik (Journal of Educational Sciences, 2026)
Mathematical reasoning ability is the capacity for logical thought in analyzing information, formulating arguments, and drawing verifiable conclusions. This study aimed to analyze the mathematical reasoning abilities of male and female ninth-grade students at SMP Negeri 19 Palu when solving word problems involving Systems of Linear Equations with Two Variables (SPLDV). A qualitative descriptive approach was employed, involving two students from class IX-C one male and one female selected purposively based on high mathematics grades in their report cards. The mathematical reasoning indicators used were based on those proposed by Vebrian: (1) making conjectures, (2) performing mathematical manipulations, (3) constructing proofs or providing reasons, and (4) drawing conclusions. Data were collected through observation, written tests, and semi-structured interviews, and subsequently analyzed qualitatively. The results revealed a difference in mathematical reasoning ability between the female and male subjects when solving SPLDV problems. The female student met all mathematical reasoning indicators and was able to correct calculation errors to arrive at the correct answer. Conversely, the male student did not meet all the indicators, particularly regarding the formulation of conjectures, and made several calculation errors. Thus, the female student demonstrated superior mathematical reasoning ability compared to the male student in solving SPLDV problems.